2005
DOI: 10.1016/j.paid.2004.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural inhibition and behavioural activation system scales for children: relationships with Eysenck’s personality traits and psychopathological symptoms

Abstract: This study examined the psychometric properties of an age-downward version of the Carver and White (1994) BIS/BAS scales. Normal school children (N = 284) aged 8-12 years completed the BIS/BAS scales as well as scales of Neuroticism, Extraversion, and psychopathological symptoms. Results showed that the BIS/BAS scales for children had a theoretically meaningful factor structure and satisfactory reliability. Relationships with EysenckÕs personality traits of Neuroticism and Extraversion, and psychopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
182
4
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(207 citation statements)
references
References 25 publications
19
182
4
2
Order By: Relevance
“…Experiment 1A showed that the size of relationship between the child adapted CW-BIS used in the present studies and another measure of general anxiety was consistent with that found in past research (e.g. Muris et al 2005). Experiment 1B sought to directly compare two child adapted versions of the CW-BIS.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Experiment 1A showed that the size of relationship between the child adapted CW-BIS used in the present studies and another measure of general anxiety was consistent with that found in past research (e.g. Muris et al 2005). Experiment 1B sought to directly compare two child adapted versions of the CW-BIS.…”
Section: Discussionsupporting
confidence: 83%
“…The SCARED is also invariant across gender (Hale et al, 2005) Children completed our adapted CW-BIS and that of Muris et al (2005) in a random order.…”
Section: Screen For Child Anxiety Related Disorders (Scared)mentioning
confidence: 99%
See 1 more Smart Citation
“…These scales measure BAS through three activational factors [22]: fun seeking (BAS FS), reward responsiveness (BAS RR), and drive (BAS DRV). Previous research has yielded evidence for the psychometric properties of the BAS scales [22][23][24][25][26]. Previous research has also, however, shown that mainly BAS RR and DRV are associated with food intake and not BAS FS [21,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that pre-existing traits, such as behavioural inhibition, leads to numerous stressful events (e.g. incarceration), which results in high levels of negative affect (e.g., Colder & O'Connor, 2004;Gudiño, Nadeem, Kataoka, & Lau, 2012;Muris, Meesters, de Kanter, & Timmerman, 2005).…”
Section: Introductionmentioning
confidence: 99%